PREDICTION AND PROVIDING MEDICATION FOR THYROID DISEASE USING MACHINE LEARNING TECHNIQUE (SVM) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thyroid disorder leading cause of medical diagnosis and prediction development, which medical science is acomplicated axiom. Thyroid gland is one of our body's main organs. Thyroid hormone secretions are responsible forregulating metabolism. Hyperthyroidism and hypothyroidism are the two prominent thyroid disorders that produce thyroidhormones for control of body metabolism. The machine learning is critical in the disease prediction process and in the studyand classification models used for thyroid disease on the basis of data obtained from hospital datasets. A decent knowledgebase must be ensured, built and used as a hybrid model to solve dynamic learning tasks like medical diagnosis andpredictional tasks. Basic techniques of machine learning are used for the identification and inhibition of thyroid. The SVM isused to predict the approximate probability of a thyroid patient.If the patient has risk of getting thyroid our system has togive suggestions like recommending home remedies, precautions, medication etc…